2021
DOI: 10.21037/apm-21-967
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of psychological resilience on self-efficacy and quality of life in patients with diabetic foot ulcers: a prospective cross-sectional study

Abstract: Background: Patients with diabetic foot ulcer (DFU) usually have a poor quality of life (QoL) and selfefficacy, which is affected by many risk factors. However, the role of psychological resilience in QoL and selfefficacy in DFU patients has remained unclear.Methods: This prospective cross-sectional study was performed in a single center from January 2018 to February 2020. A total of 98 DFU patients were enrolled in this study. Some demographic and clinical data were prospectively collected from participants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…Meanwhile, the results of this study showed that resilience was an in uential factor for the self-management e cacy of NPC radiotherapy patients (P < 0.01), and there was a positive correlation between the two, that is, the higher the level of resilience of NPC radiotherapy patients have, the better their self-management e cacy will be, which was similar to the results of the study by Kuang et al [32] . Resilience refers to the ability of patients to adapt and recover quickly in the face of negative events by using existing resources.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, the results of this study showed that resilience was an in uential factor for the self-management e cacy of NPC radiotherapy patients (P < 0.01), and there was a positive correlation between the two, that is, the higher the level of resilience of NPC radiotherapy patients have, the better their self-management e cacy will be, which was similar to the results of the study by Kuang et al [32] . Resilience refers to the ability of patients to adapt and recover quickly in the face of negative events by using existing resources.…”
Section: Discussionsupporting
confidence: 89%
“…In a study of patients with diabetes-caused foot ulcers, factors such as self-efficacy were significantly higher for the high-resilience group than for the low-resilience group ( 117 ). Self-efficacy among college students enrolled in online courses was reflected in the completion of their courses, social and academic interactions with classmates, use of the course management system, and interaction with instructors ( 118 ). Resilience can be a key factor in the psychosocial care of patients ( 119 ), and college students who experience excessive negative emotions due to the COVID-19 pandemic can improve their self-efficacy through online learning platforms that promote adaptive development.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 70 diabetic patients, 3 to 18 after amputation operation for follow up, were recruited using a purposive sample.y Data were collected using the following two tools: Tool I: Patients Structured interviewing questionnaire. This tool was developed by the investigator in simple Arabic language based on reviewing the related literatures (8,9) . It included three parts: A) Socio-demographic characteristics of patients: It was used to assess the patient's demographic characteristics including age, gender, marital status, education level, occupation status, monthly income and residence; B) Medical history of patients: It was used to assess patient's medical and family history including the following: duration of disease, type of DM, type of diabetic medication, period of hospitalization, main cause of current hospialization adimision, amputation site, complication at amputation site, history of chronic diseases, previous amputation surgery, family history of DM and amputation; C) Knowledge assessment questionnaire: This tool was adapted from Zubair et al (10) to assess the knowledge of patients regarding diabetes mellitus (7 items), diabetic foot care (21 items), and diabetic foot amputation (13 items).…”
Section: Methodsmentioning
confidence: 99%